2022
DOI: 10.3390/antibiotics11050622
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Identification of Compounds Involved in the Fungal Synthesis of AgNPs: Effect on Antimicrobial and Photocatalytic Activity

Abstract: The biological synthesis of silver nanoparticles (AgNPs) for medical, environmental, and industrial applications is considered an alternative to chemical synthesis methods. Additionally, the reducing, capping, and stabilizing molecules produced by the organisms can play a key role in the further activity of AgNPs. In this work, we evaluated the synthesis of AgNPs by four molecular weight fractions (S1: <10 kDa, S2: 10 to 30 kDa, S3: 30 to 50 kDa, and S4: >50 kDa) of mycelia-free aqueous extract produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Furthermore, certain fungi can create and release mycotoxins, which are toxic to humans and animals. To prevent such illnesses, chemical fungicides and pesticides have been utilized; nevertheless, these treatments have had a significant influence on the environment and, as a result, human health [ 45 ]. Plant extracts and plant-based AgNPs were used in this work to assess their effectiveness against four phytopathogenic Fusarium species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, certain fungi can create and release mycotoxins, which are toxic to humans and animals. To prevent such illnesses, chemical fungicides and pesticides have been utilized; nevertheless, these treatments have had a significant influence on the environment and, as a result, human health [ 45 ]. Plant extracts and plant-based AgNPs were used in this work to assess their effectiveness against four phytopathogenic Fusarium species.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, a previous study showed that the Aq-extract of R. stricta affected the mycelial growth of F. solani with a zone of inhibition (ZOI) of 16 ± 0.3 mm, where the biosynthesized AgNPs induced a ZOI of 26 ± 0.5 mm [ 36 ]. Another study showed that the methanolic extract of R. stricta affected the mycelial growth of F. solani with a ZOI of 18 mm [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total polyphenol contents (TPC) of LJTE were determined as previously described (Vera et al, 2023). A standard curve of gallic acid (Titan Scientific) was plotted as the standard (Y = 0.01166X + 0.08603, R 2 = 0.997).…”
Section: Determination Of Total Polyphenol Contentmentioning
confidence: 99%
“…The surfaces of metallic nanoparticles are easily functionalized, allowing the attachment of various molecules, such as antibodies and probes . The therapeutic applications of metallic nanoparticles have demonstrated potential in antimicrobial, anticancer, and antileishmanial activities, targeting both promastigotes and amastigotes forms of Leishmania protozoans. Their mechanism of action is primarily associated with the increased concentration of reactive oxygen species (ROS). , Within the mammalian body, the nanoparticles are recognized as pathogens and engulfed by macrophages, which maintain an acidic environment (pH ∼ 5.8) conducive to metal oxidation . The high surface-volume ratio of metallic nanoparticles facilitates a rapid rate of surface oxidation .…”
Section: Inorganic Materials To Treat Leishmaniasismentioning
confidence: 99%